Mitigating Work Alienation through Workplace Spirituality among Bank Employees in Delta State, Nigeria - Ojobu, Augusta Mary Onyebuchi (ESUT JOURNAL OF SOCIAL SCIENCES, 2024)
This study examines the role of workplace spirituality in mitigating work alienation and enhancing work engagement among bank employees in Delta State, Nigeria. In the context of Nigeria’s evolving banking sector, where reforms and competitive pressures demand high levels of employee engagement, alienation poses a significant barrier to optimal work performance. The research investigates how the dimensions of work alienation—powerlessness, meaninglessness, and self-estrangement—affect employee engagement and how workplace spirituality can serve as a moderating factor in reducing these negative effects. By integrating workplace spirituality into the organisational culture, banks may foster a more supportive environment that enhances employees’ sense of belonging, purpose, and connection to their work. Data were collected from bank employees using structured questionnaires that measured levels of work engagement, work alienation, and workplace spirituality. Findings indicate that workplace spirituality significantly moderates the negative impact of work alienation, suggesting that spiritual practices in the workplace can play a crucial role in improving employee well-being, engagement, and overall organisational productivity.